Explaining Investment in the WAEMU - Vamvakidis, Athanasios (IMF Working Papers; Working Paper, 1998)
This paper estimates an empirical model for investment in the West African Economic and Monetary Union (WAEMU), a region with relatively low investment shares, using annual data for the period 1970-95. Cross-country and time-series evidence shows that openness to international trade, competition in the domestic market, freedom of international capital transactions, and low dependency ratios are positively correlated with investment in the WAEMU region.